(untitled) (Prudentia Iuris, 2017)
The author analyzes the current state of the “paradox of dignity”. This paradox is used to describe how over the last centuries the human person was glorified but at the same time certain doctrines have been leading to the abolition of man. After a historical journey where the roots of these doctrines are located at the dawn of the Modern Age with Descartes, we reach the 20th century with its reductionist doctrines of the human person. From another perspective, the classical theory, the dignity of the human person it shows itself as rooted in its own constitutive reality.